2017
DOI: 10.1097/jom.0000000000000935
|View full text |Cite
|
Sign up to set email alerts
|

Symptoms of Nervous System Related Disorders Among Workers Exposed to Occupational Noise and Vibration in Korea

Abstract: Occupational exposures to vibration and noise are associated with NSRS. Additional longitudinal studies and tightened education and safety measures are warranted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 47 publications
(38 reference statements)
2
10
0
Order By: Relevance
“…Regarding the subgroup analysis of occupational variables and noise and vibration exposure in individuals with insomnia, men and women who did not wear PPE when required and were exposed to vibration exposure only or both noise and vibration exposure, therefore eliminating a form of protection against the two exposures, had a significantly higher risk of insomnia supporting the findings of a prior study [9]. The implications of not wearing specialized PPE such as earplugs for noise exposure or anti-vibration gloves for vibration exposure can be severe; therefore, the World Health Organization (WHO) released guidelines regarding PPE use to lessen these harmful effects [40].…”
Section: Discussionsupporting
confidence: 75%
See 3 more Smart Citations
“…Regarding the subgroup analysis of occupational variables and noise and vibration exposure in individuals with insomnia, men and women who did not wear PPE when required and were exposed to vibration exposure only or both noise and vibration exposure, therefore eliminating a form of protection against the two exposures, had a significantly higher risk of insomnia supporting the findings of a prior study [9]. The implications of not wearing specialized PPE such as earplugs for noise exposure or anti-vibration gloves for vibration exposure can be severe; therefore, the World Health Organization (WHO) released guidelines regarding PPE use to lessen these harmful effects [40].…”
Section: Discussionsupporting
confidence: 75%
“…The rationale behind investigating the effect of both noise and vibration with insomnia is that, for instance, when handling large equipment or driving large vehicles, workers are often exposed to noise and vibration simultaneously in their work environments. A prior study carried out in Korea showed that combined noise and vibration exposure had a greater effect on the increased total of nervous system-related disorders, which included headache/eyestrain, fatigue, and sleep disturbance/insomnia [9]. Therefore, there is a need to investigate the combined effect of noise and vibration.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Additionally, although vibration exposure could be divided into whole-body vibration, motion sickness, and hand-transmitted vibration [35], the survey did not include this breakdown of vibration types, potentially introducing error. Previous studies have reported that workers who do not wear personal protection devices are more easily exposed to hazardous factors such as noise or vibration [36], but this study could not adjust for the use of personal protection devices. Additionally, we could not adjust for variables such as job stress or psychosocial work environment, which have also been suggested to ergonomic risk factors [3739].…”
Section: Discussionmentioning
confidence: 99%